EMPLOYEE ENGAGEMENT AND ORGANIZATION SUPPORT STRATEGIES: THE MEDIATING ROLE OF PERCEIVED ORGANIZATION SUPPORT FOR HOLISTIC EMPLOYEE SUBJECTIVE WELL-BEING - Asan, Sucipto; Panjaitan, Andry; Suwu, Selvi Esther; Ferdinand, Ferry Vincenttius (Jurnal Aplikasi Manajemen, 2020)
Keeping employees engaged is strategically important. This paper analyzes the drivers of employee engagement from the point of view of organizational support for employee well-being. The article contains an analysis of data of 509 respondents from a faithbased higher education in Indonesia, conducted through PLS structural equation modeling analysis. The result indicates that the organization support in terms of organization internal communication, performance-based reward and recognition, and perceived organization support on holistic employee subjective well-being has a direct positive influence on employee engagement. The perceived organization support on holistic employee subjective well-being played a mediating role between employee engagement and teamwork dynamic, supervisor support, and work environment. The findings imply theory and practice especially in enhancing employee engagement experience through organizational support. For future research, we suggest including more various organizations and industries to better understand the variable interdependencies in various contexts.